Rural households’ access to microcredit and poverty status in Obafemi- Owode Local Government Area of Ogun State, Nigeria (2008)
This study examined the effect of access to micro-cred it on poverty status of rural households in Obafemi -Owode LGA in Ogun state, employing data collected from 94 randomly selected households in the study area. Data were analysed with the aid of FGT poverty index and the Logit regression model. The results of descriptive analysis reveal that majority of the poor households in the study area were large sized, male headed with no formal education and no access to credit. The head count poverty index also reveals that about 35 percent of households in the study area were poor, subsisting below the poverty line of 6,279.33 naira per capital per month. The econometric analysis shows that age, house hold size, secondary and tertiary education of household head, access to credit and sector of primary occupation of the household head were the significant factors that determine poverty status in the study area. The study concludes that poverty reduction in the rural areas requires effective t a r get in g with educational programmes a n d most importantly, availability and accessibility of rural households to credit facilities in order to improve their income earning opportunities thereby enhancing their welfare.